2020
DOI: 10.1111/gcb.14951
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis on the potential for increasing nitrogen losses from intensifying tropical agriculture

Abstract: Fertilized temperate croplands export large amounts of reactive nitrogen (N), which degrades water and air quality and contributes to climate change. Fertilizer use is poised to increase in the tropics, where widespread food insecurity persists and increased agricultural productivity will be needed, but much less is known about the potential consequences of increased tropical N fertilizer application. We conducted a meta‐analysis of tropical field studies of nitrate leaching, nitrous oxide emissions, nitric ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 61 publications
1
41
0
Order By: Relevance
“…However, doubling fertilizer levels from 80 to 160 kg N ha ‒1 yr ‒1 in soybean–maize double‐cropped systems increased NO fluxes by an order of magnitude, from 0.6 to 6.7 kg N ha ‒1 mo ‒1 , which would roughly scale to 1.1 and 7.4 kg N ha ‒1 yr ‒1 , much higher than most observations from a NO fluxes at a 160‐kg N ha ‒1 yr ‒1 fertilization rate that were typically <2 kg N ha ‒1 yr ‒1 at the same fertilization rate in a global meta‐analysis (Huddell et al., 2020). Nitric oxide fluxes of 7.4 kg N ha ‒1 yr ‒1 exceeded the expected value for NO fluxes at a 160‐kg N ha ‒1 yr ‒1 fertilization rate, but well within the range of observations from a global meta‐analysis on fertilized croplands (Huddell et al., 2020). In the high fertilization treatment, our hourly NO flux measurements were among the highest ever measured in agricultural systems, comparable with the record highs reported in Matson (1998) and Oikawa et al.…”
Section: Summary and Concluding Thoughtsmentioning
confidence: 86%
See 2 more Smart Citations
“…However, doubling fertilizer levels from 80 to 160 kg N ha ‒1 yr ‒1 in soybean–maize double‐cropped systems increased NO fluxes by an order of magnitude, from 0.6 to 6.7 kg N ha ‒1 mo ‒1 , which would roughly scale to 1.1 and 7.4 kg N ha ‒1 yr ‒1 , much higher than most observations from a NO fluxes at a 160‐kg N ha ‒1 yr ‒1 fertilization rate that were typically <2 kg N ha ‒1 yr ‒1 at the same fertilization rate in a global meta‐analysis (Huddell et al., 2020). Nitric oxide fluxes of 7.4 kg N ha ‒1 yr ‒1 exceeded the expected value for NO fluxes at a 160‐kg N ha ‒1 yr ‒1 fertilization rate, but well within the range of observations from a global meta‐analysis on fertilized croplands (Huddell et al., 2020). In the high fertilization treatment, our hourly NO flux measurements were among the highest ever measured in agricultural systems, comparable with the record highs reported in Matson (1998) and Oikawa et al.…”
Section: Summary and Concluding Thoughtsmentioning
confidence: 86%
“…The relationships between N fertilizer use and fluxes of NO and N 2 O are fairly well established in temperate agroecosystems, but unintended N losses from fertilizer are poorly understood in tropical croplands. A recent meta‐analysis identified only 11 studies with NO measurements from fertilized agricultural systems in the tropics (Huddell et al., 2020). Although across the global tropics increased fertilizer use results in larger emissions of N 2 O and NO, these emissions are highly variable from site to site (Huddell et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fate of the increase in N fertilizer to croplands in SSA and other tropical regions is not well studied and is a high priority research area for the next decade. Recently, a metaanalysis of the risk for increasing N losses from intensifying tropical agriculture, including in SSA, concluded that inputs from 50 to 150 kg N ha -1 year -1 would have substantial environmental consequences and lead to large increases in NO 3 leaching and gaseous nitrogen fluxes to the atmosphere from many, but not all tropical soils (Huddell et al 2020). Soil orders such as Oxisols and some Ultisols, which cover about 20% of SSA (Eswaran et al 1998), have net anion exchange capacity that decreases NO 3 leaching into the environment (Russo et al 2017).…”
Section: Research Challenges For the Coming Decadesmentioning
confidence: 99%
“…However, higher total energy content of diets can also increase methane production per animal [17] . Other risks include increasing CO 2 emissions from expanding cropland areas [18] and N 2 O emissions from intensi cation of feed crop production [19] . Changes in feeding practices can also lead to land sparing by substituting low yielding grass and forages with higher yielding feed crops, for which regional and global studies have suggested can reduce grassland requirements [20] and reduce deforestation [21] .As an estimated 96% of cattle in Tanzania are reared in extensive grazing systems [22] , we hypothesized that land sparing is a leading strategy for reducing dairy emissions.…”
Section: Introductionmentioning
confidence: 99%